Mobile Phone Penetration, Mobile Banking and Inclusive Development in Africa - Simplice Asongu; Jacinta C. Nwachukwu (African Governance and Development Institute (AGDI), 2016)
The study assesses the role of mobile phones and mobile banking in decreasing inequality in 52 African countries. The empirical procedure involves first, examining the income-redistributive effect of mobile phone penetration and then investigating the contribution of mobile banking services in this relationship. The findings suggest an equalizing income-redistributive effect of `mobile phone penetration' and `mobile banking', with a higher income-equalizing effect from mobile banking compared to mobile phone penetration. Poverty alleviation channels explaining this difference in inequality mitigating propensity are discussed.
Keywords: E00; G20; L96; O17; O33; 330; Banking; Mobile Phones; Shadow Economy; Financial Development; Africa